CHARACTERISTICS OF TIDES, WAVES, AND BATHYMETRY IN THE WATERS OF BAYUR BAY PADANG CITY, WEST SUMATRA - Rafly Fadiansyah Siregar; Rifardi Rifardi; Efriyeldi Efriyeldi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
This study aims to examine the characteristics of tides, waves, and bathymetry in Bayur Bay, Padang City, West Sumatra. Data collection was conducted in October 2024 through a survey method that included tidal observations for 15 days, wave measurements at three stations for 3 days, and measurements of water quality parameters (temperature, salinity, and brightness). Secondary data were obtained from ECMWF and GEBCO and analyzed using Surfer 13 and ArcGIS. The analysis results show that the tides are of a mixed type, leaning towards double daily with a Formzahl value of 0.51. Wave heights vary between 0.15 and 0.6 m, and validation with ECMWF data yields low RMSE values (0.1263-0.2983), indicating the suitability of the model and field data. The bathymetry of Bayur Bay ranges from 0 to 45 m, with the seabed dominated by fine sand. This information is important as a basis for coastal zone management, shipping, and maritime infrastructure development